2011
DOI: 10.1186/1752-1947-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant mixed Müllerian tumor arising from the mesorectum with a synchronous ovarian cancer: a case report and review of the literature

Abstract: IntroductionExtragenital malignant mixed Müllerian tumor is an extremely rare presentation of malignant mixed Müllerian tumor, especially when combined with a synchronous ovarian cancer.Case presentationWe report the clinical course and pathologic findings of a case of mesorectal malignant mixed Müllerian tumor with synchronous ovarian cancer, in a 50-year-old, gravida 0, para 0, Han Chinese woman with regular menstruation. This is the sixteenth case in the English literature of extragenital malignant mixed Mü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The other reported tumours found in the mesorectum are a solitary fibrous tumour, gastrointestinal stromal tumour, malignant mixed Mullerian tumour with biphasic differentiation (adenocarcinomatous and spindle cell sarcomatous elements), malignant fibrous histiocytoma, the malignant and metastatic lesion from colon and breast . However, our patient's histopathological study showed squamous epithelium with keratinization rather than mesenchymal cells such as the interstitial cell of Cajal, fibroblast, atypical giant cells or histiocyte‐like cells, thereby ruling out the aforementioned differential diagnoses.…”
mentioning
confidence: 50%
“…The other reported tumours found in the mesorectum are a solitary fibrous tumour, gastrointestinal stromal tumour, malignant mixed Mullerian tumour with biphasic differentiation (adenocarcinomatous and spindle cell sarcomatous elements), malignant fibrous histiocytoma, the malignant and metastatic lesion from colon and breast . However, our patient's histopathological study showed squamous epithelium with keratinization rather than mesenchymal cells such as the interstitial cell of Cajal, fibroblast, atypical giant cells or histiocyte‐like cells, thereby ruling out the aforementioned differential diagnoses.…”
mentioning
confidence: 50%
“…Exploratory laparotomy with surgical staging and a detailed pathological examination clinches the diagnosis of multiple primary tumors. A recurrence of the tumor had been documented in these patients when no adjuvant therapy was given after the surgical resection …”
Section: Discussionmentioning
confidence: 99%
“…The majority of synchronous genital primary malignancies are endometrial and ovarian tumors . Synchronous presentations of MMMT in extra‐genital sites (mesentery, mesorectum, broad ligament) with ovarian adenocarcinoma have been reported . Exploratory laparotomy with surgical staging and a detailed pathological examination clinches the diagnosis of multiple primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It was considered that the biological behavior of PRMA resembled that of epithelial ovarian cancer, so patients have been treated in a similar way, using the same regimen of adjuvant chemotherapy for ovarian tumors; the role of radiotherapy remains controversial [ 1 , 11 , 12 ]. As shown in the literature, because of the very small number of cases thus far presented, no evidence-based management guidelines are available.…”
Section: Discussionmentioning
confidence: 99%
“…A malignant mixed müllerian tumor (MMMT) that develops from the female genital tract is a rare clinical entity, accounting for less than 1% of all gynecological malignancies [ 1 ]. Since müllerian ducts develop to form the fallopian tubes, uterus and the upper third of the vagina, MMMTs are usually found in these structures or, sometimes, in the ovary.…”
Section: Introductionmentioning
confidence: 99%